Development of T-Solve Interactive Learning Media with Polya Approach on Pythagorean Theorem - Putri, Vika Amelia; Aziz, Abdul; Suprayitno, Iswahyudi Joko (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
Mathematics learning in schools is often dominated by conventional methods, resulting in passive student participation and low conceptual understanding, especially in topics such as the Pythagorean Theorem. This study aims to develop and evaluate the effectiveness of “T-SOLVE,” an interactive learning media based on Polya’s problem-solving approach, in enhancing students’ understanding of the Pythagorean Theorem. The research employed a Research and Development (R&D) method using the ADDIE model. The sample consisted of eighth-grade students at SMP Negeri 2 Sumowono. Data were collected through expert validation sheets, student response questionnaires, and tests to measure learning outcomes. The results indicate that the T-SOLVE media is valid, practical, and effective in improving students’ conceptual understanding and engagement. The media’s integration of problem-solving steps supports students in learning independently and applying concepts to real-life situations. The implication of this research is that T-SOLVE can be used as an alternative learning resource that promotes interactive, student centered learning, which addresses the initial problem of passive learning and low motivation. Furthermore, it contributes to improving mathematical problem solving skills and serves as a relevant tool for 21st century learning.